Oblicz wartość liczbową wyrażenia.

a) -y + 8x - z - 2x dla x= -2, y= 6, z= -3
b) -8y - 4z + x - y - 2z + 1 dla x= -0,5, y= -1, z = 2
c) 9y - (7y + x ) + ( 6x - 7y ) dla x= -2, y = 0,1
d) (6a - 8b - 0,7) - (6,9 + a - 5b) + 1,8 dla a= 0,2, b= 0,1
e) 1/2abc - (4ab + 2abc ) + ( -bc + 5ab ) dla a= -2, b= 1/2, c= -4

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-20T13:37:47+01:00
A)
-y + 8x - z - 2x =
-y+6x-z =
-6+6*(-2)-(-3) =
-6-12+3 =
-15

b)
-8y - 4z + x - y - 2z + 1 =
-9y-6z+x+1 =
-9*(-1)-6*2+(-0,5)+1 =
9-12-0,5+1 =
-2,5

c)
9y - (7y + x ) + ( 6x - 7y ) =
9y-7y-x+6x-7y =
-5y+5x =
-5*0,1+5*(-2) =
-0,5-10 =
-10,5

d)
(6a - 8b - 0,7) - (6,9 + a - 5b) + 1,8 =
6a-8b-0,7-6,9-a+5b+1,8 =
5a-3b-0,7-6,9+1,8 =
5*0,2-3*0,1-0,7-6,9+1,8 =
1-0,3-0,7-6,9+1,8 =
-5,1

e)
1/2abc - (4ab + 2abc ) + ( -bc + 5ab ) =
½abc-4ab-2abc-bc+5ab =
-1½abc+ab-bc =
-1½*(-2)*½*(-4)+(-2)*½-½*(-4) =
-6-1+2 =
-5
10 4 10
2010-03-20T13:42:28+01:00
A)
-6+8•(-2)-(-3)-2•(-2)=-6-16+3+4=-15
b)
-8•(-1)- 4•2+(-0,5)-(-1)- 2• 2+1=8-8-0,5+1-4+1=-2,5
c)
9•0,1-(7•0,1+(-2))+(6•(-2)-7•0,1)=0,9-(0,7-2)+(-12-0,7)=0,9-(-1,3)-12,7=-1,5
d)
(6•0,2-8•0,1-0,7)-(6,9+0,2)-5•0,1+1,8=(1,2-0,8-0,7)-7,1-0,5+1,8=-0.3-8,4=-8,7
e)
½•(-2)•½•(-4)-(4•(-2)•½+2•(-2)•½•(-4))+(-½•(-4)+5•(-2)•½)=2-(-4+8)+(2-5)=2+4-3=3
5 3 5